Skin rash in metastatic hormone sensitive prostate cancer patients treated with apalutamide: a retrospective multicenter study in Korea - Won Tae Kim; Hyun Ho Han; Seok Joong Yun; Seong Hyeon Yu; Taek Won Kang; Yun-Sok Ha; Jun Nyung Lee; Tae Gyun Kwon; Byung Hoon Kim; Won Ik Seo; Chan Ho Lee; Jae Il Chung; et al. (Prostate International)
Background: Skin rash is a common adverse event in patients with metastatic hormone-sensitive prostate cancer (mHSPC) treated with apalutamide. This study aims to investigate the incidence rate of skin rash and the predictive value of inflammation markers for skin rash in real-world Korean patients. Materials and Methods: We conducted a retrospective analysis of patients with prostate cancer (PCa) who received apalutamide across 18 institutions in Korea, with a follow-up period of at least three months. A total of 218 patients were evaluated. Results: Among the 214 patients analyzed, 78 (36.4%) developed a skin rash. The severity of the rash was classified as grade 1 (G1) in 27 patients (12.6%), grade 2 (G2) in 29 patients (13.5%), and grade 3 (G3) in 22 patients (10.3%). The median time to onset of any skin rash was 65.5 days (interquartile range, IQR 31.0-88.0). The monocyte-to-lymphocyte ratio (MLR) and systemic immune-inflammation response index (SIRI) were significantly higher in the G2 plus G3 group compared to the no rash plus G1 group (p=0.006, p=0.013, respectively) before apalutamide treatment. After 3 months, platelet-to-lymphocyte ratio (PLR) and SIRI were significantly higher in the G2 plus G3 group compared to the no rash plus G1 group (p=0.010, p=0.025, respectively) Conclusions: In a real-world cohort of Korean patients, skin rash occurred in 36.4% of cases, with a median time to onset of 65.5 days. Grade 3 skin rash developed in 10.3% of cases. While MLR and SIRI were significantly higher in the G2 plus G3 group, these markers cannot be considered reliable predictors due to a low area under the curve (AUC < 0.7) before apalutamide treatment. However, increased levels of PLR, SII, and SIRI could potentially be useful for monitoring for the risk of severe rash development in these patients.